Preparation method and application of FTO catalyst for effectively inhibiting CO2

Through the preparation of the domain-limited and eggshell type Co-based catalyst, the problem of high CO2 selectivity in Fischer-Tropsch synthesis is solved, and the CO2 selectivity is efficiently reduced and olefin selectivity is improved, which is suitable for industrial applications.

CN120438013APending Publication Date: 2025-08-08SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510583452.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-07
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

The CO2 selectivity of existing Co2C-based catalysts is too high in the olefin reaction of Fischer-Tropsch synthesis, reaching more than 40%, and it is necessary to effectively reduce CO2 selectivity to improve economicality and efficiency.

Method used

The catalyst is prepared by impregnation method, precipitation method and hydrothermal method using the combination of Co, M1 and M2 oxides to regulate the catalyst structure and component existence mode to reduce CO2 selectivity.

Benefits of technology

It significantly reduces CO2 selectivity to 12.8%, maintains high CO conversion and olefin selectivity, has good catalyst stability, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005391019560000101
    Figure BDA0005391019560000101
  • Figure BDA0005391019560000111
    Figure BDA0005391019560000111
Patent Text Reader

Abstract

The invention provides a preparation method and application of an FTO catalyst for effectively inhibiting CO2. The purpose of reducing the CO2 selectivity is achieved by modifying the FTO catalyst; wherein the catalyst modification scheme comprises the modification of a confinement type catalyst and the modification of an eggshell structure catalyst, and the result shows that the modification process disclosed by the invention has relatively excellent comprehensive catalytic performance, relatively high olefin selectivity in product distribution, relatively economical efficiency in product distribution and relatively low by-product CO2, and the lowest CO2 selectivity can reach 12.8%; moreover, the modification process disclosed by the invention is relatively good in stability, the activity of the catalyst is not obviously inactivated within 2000h, meanwhile, the modification process is relatively simple, and industrial application can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a preparation method and application of a FTO catalyst that effectively inhibits CO2. Background Art

[0002] Synthesis gas, derived from coal, consists primarily of CO and H₂, serving as a fundamental raw material in the chemical industry. The Fischer-Tropsch pathway, which produces a range of high-value-added products such as alcohols, olefins, and alkanes, is a key chemical raw material. Olefins, including both low-carbon and high-carbon olefins, are important raw materials in the chemical industry. Direct olefin production from syngas via the Fischer-Tropsch pathway has attracted widespread attention in the chemical industry due to its advantages, including simplicity and ease of operation. Prismatic cobalt carbide catalysts with specific exposed crystal faces have been demonstrated in numerous studies for their potential application in the efficient production of olefins from syngas and are considered to have significant industrial value. However, currently developed Co₂C-based catalysts, in addition to their high activity and olefin selectivity under mild reaction conditions, exhibit significant water-gas shift activity, resulting in high CO₂ selectivity exceeding 40%. CO₂ is a byproduct of the Fischer-Tropsch synthesis reaction, making effectively reducing CO₂ selectivity a key challenge in Co₂C-based olefin production catalysts.

[0003] In the existing Fischer-Tropsch process, a series of modifications and adjustments to the active metal components or catalyst structure can effectively improve the catalytic performance of the catalyst. Common modification methods include the addition of electronic and structural additives. Catalyst structure adjustment includes changes in morphology, crystal structure, and the presence of various components.

[0004] Co2C-based catalysts for direct synthesis of olefins from syngas are subject to stricter requirements for catalyst modification and structural control due to their metastable nature. Therefore, there is an urgent need for a Co2C-based catalyst that can effectively reduce CO2 selectivity. Summary of the Invention

[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a method for preparing a FTO catalyst that can effectively inhibit CO2, so as to solve the problem of high CO2 selectivity in the FTO reaction in the prior art.

[0006] To achieve the above-mentioned purpose and other related purposes, the present invention is achieved through the following technical solutions.

[0007] In a first aspect of the present invention, a Co-based catalyst is provided, comprising an active component and a carrier, wherein the active component comprises Co oxide and M1 oxide, wherein M1 comprises one or more of Mn, Na, and Al, and the molar ratio of Co to M1 is 1:10 to 10:1; the Co-based catalyst is a confined Co-based catalyst or an eggshell-type Co-based catalyst.

[0008] In some embodiments of the present invention, the molar ratio of Co to M1 may also be 1:10-1:5, 1:5-1:2, 1:2-1:1, 1:1-2:1, 2:1-3:1, 3:1-5:1, 5:1-7:1 or 7:1-10:1.

[0009] In some embodiments of the present invention, M1 in the confined catalyst further includes one or more of Ce, Zr, and K.

[0010] In some embodiments of the present invention, the active component in the confined catalyst further includes M2 oxide, wherein the M2 oxide serves as a modification aid to modify the catalyst.

[0011] In some embodiments of the present invention, the molar ratio of Co to M2 is selected from 3:1 to 30:1; it can also be 3:1 to 6:1, 6:1 to 9:1, 9:1 to 12:1, 12:1 to 15:1, 15:1 to 18:1, 18:1 to 21:1, 21:1 to 24:1, 24:1 to 27:1, 27:1 to 30:1.

[0012] In some embodiments of the present invention, the M2 includes one or more of alkali metal elements, alkaline earth metal elements, noble metals, and rare earth metal elements.

[0013] In some embodiments of the present invention, the alkali metal element includes one or more of Na, Li, K, Rb, and Cs.

[0014] In some embodiments of the present invention, the alkaline earth metal element includes one or more of Mg, Ca, Ba, Be, and Sr.

[0015] In some embodiments of the present invention, the noble metal element includes one or more of Au, Ag, and Pt.

[0016] In some embodiments of the present invention, the rare earth metal element includes one or more of La, Nd, Pr, and Y.

[0017] In some preferred embodiments of the present invention, the M2 is selected from one or more of Mg, Ca, Ba, Ru, and La.

[0018] In some embodiments of the present invention, the carrier component is selected from one or more of SiO2, Al2O3, and activated carbon.

[0019] In some embodiments of the present invention, the mass percentage of the carrier to the Co-based catalyst is 70% to 80%, and can also be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%.

[0020] In some embodiments of the present invention, in the confined catalyst, the active components (such as Co, M1, and M2 oxides) are directly confined on the surface of the carrier; in the eggshell catalyst, it includes a core and a shell coated on its surface, wherein the active components (such as Co and M1 metal oxides) serve as the core and the carrier serves as the shell material.

[0021] In some embodiments of the present invention, M1 in the eggshell-type catalyst further comprises one or more of alkaline earth metal elements, noble metals, rare earth metal elements, Si, and Al.

[0022] In some embodiments of the present invention, the alkali metal element includes one or more of Na, Li, K, Rb, and Cs.

[0023] In some embodiments of the present invention, the alkaline earth metal element includes one or more of Mg, Ca, Ba, Be, and Sr.

[0024] In some embodiments of the present invention, the noble metal element includes one or more of Au, Ag, and Pt.

[0025] In some embodiments of the present invention, the rare earth metal element includes one or more of La, Nd, Pr, and Y.

[0026] In some preferred embodiments of the present invention, M1 in the eggshell-type catalyst is one or more of Mn, Mg, Na, and Ba.

[0027] The second aspect of the present invention provides a method for preparing the Co-based catalyst described in the first aspect of the present invention, wherein the preparation method of the confined Co-based catalyst comprises one or more of an impregnation method, a precipitation method, a hydrothermal method, and a reduction method.

[0028] In some preferred embodiments of the present invention, the preparation method of the Co-based catalyst includes one or more of an equal volume impregnation method, a deposition precipitation method, an aqueous phase reduction method, and a hydrothermal method.

[0029] In some embodiments of the present invention, the confined Co-based catalyst is prepared by an impregnation method or a deposition precipitation method;

[0030] The method for preparing the catalyst by impregnation method comprises the following steps:

[0031] S11: providing soluble salts corresponding to Co, M1 and / or M2, and mixing them with a solvent to obtain a first mixed solution;

[0032] S12: impregnate an equal volume of the first mixed liquid on the carrier, and then dry and calcine.

[0033] The method for preparing the catalyst by sedimentation precipitation method comprises the following steps:

[0034] S21: providing soluble salts corresponding to Co, M1 and / or M2, and mixing them with a solvent to obtain a second mixed solution;

[0035] S22: The second mixed solution and the precipitant are co-precipitated on the carrier for sedimentation. After the precipitation is completed, the precipitate is aged, ball-milled, mixed, dried, and calcined.

[0036] In some embodiments of the present invention, the soluble salts of Co, M1, and M2 include one or more of corresponding nitrates, chlorides, sulfates, and carbonates; but are not limited thereto.

[0037] In some embodiments of the present invention, the concentration of total metal ions in the first mixed solution is 0.5-5 mol / L; it can also be 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, or 0.5-5 mol / L.

[0038] In some embodiments of the present invention, the solvent is one or a combination of water, ethanol, isobutanol, and ammonia.

[0039] In some embodiments of the present invention, the drying temperature in step S12 or S22 is 80-150°C, and can also be 80-90°C, 90-100°C, 100-110°C, 110-120°C, 120-130°C, 130-140°C or 140-150°C.

[0040] In some embodiments of the present invention, the drying time in step S12 or S22 is 5 to 20 hours, or may be 5 to 9 hours, 9 to 13 hours, 13 to 16 hours, 16 to 18 hours, or 18 to 20 hours.

[0041] In some embodiments of the present invention, the calcination temperature is 300°C to 370°C, and may also be 300°C to 310°C, 310°C to 330°C, 330°C to 350°C, or 350°C to 370°C.

[0042] In some embodiments of the present invention, the calcination time is 2 to 10 hours, and may also be 2 to 4 hours, 4 to 6 hours, 6 to 8 hours, or 8 to 10 hours.

[0043] In some embodiments of the present invention, the concentration of total metal ions in the second mixed solution is 0.5-5 mol / L; it can also be 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, or 0.5-5 mol / L.

[0044] In some embodiments of the present invention, the precipitant is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and an aqueous ammonia solution.

[0045] In some embodiments of the present invention, the concentration of the precipitant solution is 0.5-5 mol / L; it can also be 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, or 0.5-5 mol / L.

[0046] In some embodiments of the present invention, the volume ratio of the second mixed solution to the precipitant solution is 1:0.5-3; it can also be 1:0.5-1, 1-1-1.5, 1:1.5-2, 1:2-2.5, 1:2.5-3.

[0047] In some embodiments of the present invention, the coprecipitation conditions are:

[0048] The coprecipitation temperature is 20-40°C, and may also be 20-25°C, 25-30°C, 30-35°C or 35-40°C; the coprecipitation pH is 7-9, and may also be 7, 7.5, 8, 8.5 or 9.

[0049] In some embodiments of the present invention, the aging temperature is 20-40°C; it can also be 20-25°C, 25-30°C, 30-35°C, or 35-40°C.

[0050] In some embodiments of the present invention, the aging time is 1 to 3 hours; it can also be 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.

[0051] In some embodiments of the present invention, the specific step of ball milling and mixing includes: mixing the aged precipitate with grinding balls and / or grinding aids and then performing ball milling and mixing in a ball mill.

[0052] In some embodiments of the present invention, the mass ratio of the precipitate to the grinding balls is 1:5-20, or 1:5-8, 1:8-12, 1:12-15, 1:15-18, or 1:18-20.

[0053] In some embodiments of the present invention, the grinding aid is at least one of water or an organic solvent.

[0054] In some embodiments of the present invention, the mass ratio of the precipitate to the grinding aid is 1:50-200; it can also be 1:50-100, 1:100-150, or 1:150-200.

[0055] In some embodiments of the present invention, the eggshell catalyst is prepared by a hydrothermal method, which specifically comprises the following steps:

[0056] S31: providing soluble salts corresponding to Co and M1, and mixing them with a solvent to obtain a third mixed solution;

[0057] S32: evaporating the third mixed liquid to dryness to obtain a catalyst precursor;

[0058] S33: uniformly dispersing the catalyst precursor in a fourth mixed liquid comprising a silicon source, ammonia water and water, and heating the mixture. After the heating is completed, the mixture is centrifuged, dried and calcined.

[0059] In some embodiments of the present invention, the soluble salts corresponding to the cobalt and M1 include one or more of nitrate, chloride, sulfate, and carbonate; but are not limited thereto.

[0060] In some embodiments of the present invention, the solvent is one or a combination of water, ethanol, isobutanol, and ammonia.

[0061] In some embodiments of the present invention, the silicon source includes one or more of tetraethyl orthosilicate, ethyl orthosilicate, dichlorodimethylsilane, methyltrimethoxysilane, and octadecyltrimethylsilane.

[0062] In some embodiments of the present invention, the concentration of total metal ions in the third mixed solution is 0.5-5 mol / L; it can also be 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L, 0.5-5 mol / L.

[0063] In some embodiments of the present invention, the volume ratio of the silicon source, ammonia water and water in the fourth mixed liquid is 1:2~8:20~40, wherein the volume ratio of the silicon source and ammonia water can also be 1:2~4, 1:4~6 or 1:6~8; the volume ratio of the silicon source and water can also be 1:20~25, 1:25~30, 1:30~35 or 1:35~40.

[0064] In some embodiments of the present invention, the mass ratio of the catalyst precursor to the fourth mixed liquid is 1:80-150; it can also be 1:80-100, 1:100-120, or 1:120-150.

[0065] In some embodiments of the present invention, the evaporation temperature in step S32 is 130-170°C, and may also be 130-140°C, 140-150°C, 150-160°C, or 160-170°C.

[0066] In some embodiments of the present invention, the evaporation time in step S32 is 1 to 4 hours; it can also be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours.

[0067] In some embodiments of the present invention, the heating temperature in step S33 is 160-220°C, and may also be 160-170°C, 170-180°C, 180-190°C, 190-200°C or 200-220°C.

[0068] In some embodiments of the present invention, the heating time in step S33 is 8 to 14 hours, and can also be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, or 14 hours.

[0069] In some embodiments of the present invention, the centrifugation condition in step S33 is 3000-6000 r / min for 4-10 min.

[0070] In some embodiments of the present invention, the centrifugal speed in step S33 may also be 3000-4000 r / min, 4000-5000 r / min, or 5000-6000 r / min.

[0071] In some embodiments of the present invention, the centrifugation time in step S33 can also be 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.

[0072] In some embodiments of the present invention, the drying temperature in step S33 is 80-150°C, and may also be 80-90°C, 90-110°C, 110-130°C, or 130-150°C.

[0073] In some embodiments of the present invention, the drying time in step S33 is 10 to 20 hours, and can also be 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, or 20 hours.

[0074] In some embodiments of the present invention, the calcination temperature in step S33 is 300°C to 400°C, and can also be 300°C to 320°C, 320°C to 340°C, 340°C to 360°C, 360°C to 380°C, or 380°C to 400°C.

[0075] In some embodiments of the present invention, the calcination time in step S33 is 3 to 10 hours, and can also be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.

[0076] The present invention also provides the use of the above-mentioned Co-based catalyst in the preparation of olefins by FTO reaction.

[0077] Preferably, the application specifically includes the following steps: mixing the above-mentioned Co-based catalyst with quartz sand, loading the mixture into a reactor, reducing the loaded catalyst under a reducing atmosphere, and then introducing synthesis gas to react.

[0078] In some embodiments of the present invention, the mesh size of the Co-based catalyst is 30-80 mesh; it can also be 30-40 mesh, 40-50 mesh, 50-60 mesh, 60-70 mesh or 70-80 mesh.

[0079] In some embodiments of the present invention, the mesh size of the quartz sand is 30-80 mesh; it can also be 30-40 mesh, 40-50 mesh, 50-60 mesh, 60-70 mesh or 70-80 mesh.

[0080] In some embodiments of the present invention, the mass ratio of the Co-based catalyst to quartz sand is 1:0.5-3; it can also be 1:0.5-1, 1:1-2, or 1:2-3.

[0081] In some embodiments of the present invention, the preparation method further comprises reducing the catalyst before use. Preferably, the reduction conditions include: under a reducing atmosphere; a temperature of 250-400°C; a pressure of atmospheric pressure to 4 MPa; and / or a reduction space velocity of 4000-12000 ml.g -1 .h -1 ; and / or the reduction time is 3 to 40 hours.

[0082] The reduction temperature can also be 250-280°C, 280-310°C, 310-330°C, 330-360°C, 330-380°C, 380-400°C; the reduction space velocity can also be 4000-6000ml.g -1 .h -1 , 6000-8000ml.g -1 .h -1 ,8000-10000ml.g -1.h -1 10000-12000ml.g -1 .h -1 The reduction pressure can also be normal pressure (1 bar) ~ 1MPa, 1 ~ 2MPa, 2 ~ 3MPa, 3 ~ 4MPa; the reduction time can also be 3 ~ 9h, 9 ~ 15h, 15 ~ 20h, 20 ~ 25h, 25 ~ 30h, 30 ~ 35h, 35 ~ 40h.

[0083] In some embodiments of the present invention, the reducing atmosphere includes but is not limited to a mixture of H2 and N2; preferably 8-12% H2 / N2 (v / v).

[0084] In some embodiments of the present invention, the synthesis gas includes CO and H2, and the molar ratio of H2 to CO is 0.1-5, and can also be 0.1-0.5, 0.5-1, 1-2, 2-3, 3-4 or 4-5.

[0085] In some embodiments of the present invention, the reaction temperature is 200-300°C; it can also be 200-220°C, 220-240°C, 240-260°C, 260-280°C, or 280-300°C.

[0086] In some embodiments of the present invention, the reaction pressure is normal pressure to 4 MPa; it can also be normal pressure to 1 MPa, 1 to 2 MPa, 2 to 3 MPa, or 3 to 4 MPa.

[0087] In some embodiments of the present invention, the reaction space velocity is 500 to 6000 ml.g -1 .h -1 , can also be 500~1000ml.g -1 .h -1 1000~2000ml.g -1 .h -1 2000~3000ml.g -1 .h -1 3000~4000ml.g -1 .h -1 5000~6000ml.g -1 .h -1 .

[0088] In some embodiments of the present invention, the application includes one or more of the following:

[0089] 1) The CO conversion rate in olefin production from synthesis gas is 48.3-72.2%;

[0090] 2) The selectivity of CO2 in olefin production from synthesis gas is 12.8-33.3%;

[0091] 3) The selectivity of olefins in the preparation of olefins from synthesis gas is 58.3-66.9%.

[0092] The present invention provides a preparation method and application of an FTO catalyst that effectively inhibits the generation of CO2. The purpose of reducing CO2 selectivity is achieved by modifying the FTO catalyst. The catalyst modification scheme includes modification of a carrier-confined catalyst and modification of a hydrophobic eggshell structure catalyst. The results show that the modification process of the present invention has relatively excellent comprehensive catalytic performance, high olefin selectivity in product distribution, more economical product distribution, low by-product CO2, and the lowest CO2 selectivity can reach 12.8%. Moreover, the modification process of the present invention has good stability, and no obvious deactivation of the catalyst activity occurs within 2000 hours. At the same time, the modification process is relatively simple and can be industrially applied. DETAILED DESCRIPTION

[0093] The following describes the embodiments of the present invention through specific examples. Those skilled in the art will readily understand the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention.

[0094] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0095] Furthermore, it should be understood that the one or more method steps mentioned in the present invention do not exclude the presence of other method steps before or after the combination step, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified. It should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the presence of other devices / apparatuses before or after the combination device / apparatus, or the insertion of other devices / apparatuses between two explicitly mentioned devices / apparatuses, unless otherwise specified. Furthermore, unless otherwise specified, the numbering of each method step is merely a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be considered within the scope of the present invention.

[0096] [Example 1]

[0097] Co(NO₃)₂﹒6H₂O, a 50wt% aqueous solution of Mn(NO₃)₂, and Mg(NO₃)₂﹒6H₂O were dissolved in water at a Co / Mn / Mg atomic ratio of 2:1:0.5 to create a mixed salt solution with a total metal ion concentration of 2 mol / L. A 2 mol / L aqueous solution of anhydrous Na₂CO₃ was also added as a precipitant. The mother liquor was an aqueous solution dispersed in Al₂O₃, with the Al₂O₃ support accounting for 80% of the total catalyst mass.

[0098] The Co / Mn / Mg mixed solution and a Na2CO3 aqueous solution were co-precipitated in a stirred Al2O3 mother liquor at a volume ratio of 1:1. The stirred precipitation solution was maintained at a pH of 8 and a temperature of 30°C. After precipitation, the solution was aged at 30°C for 2 hours. The precipitate was then ball-milled in a ball mill using aluminum-zirconium grinding balls at a 1:10 weight ratio of precipitate to grinding balls. Water was used as a grinding aid at a 100:1 weight ratio of water to precipitate. The mixture was ball-milled for 2 hours at room temperature. After ball-milling, the mixture was dried at 120°C for 10 hours. The mixture was then calcined in a muffle furnace at 350°C for 5 hours to obtain a confined catalyst.

[0099] [Example 2]

[0100] Co(NO₃)₂﹒6H₂O, a 50% aqueous solution of Mn(NO₃)₂, Al(NO₃)₃, and Ba(NO₃)₂ were dissolved in water at a Co / Mn / Al / Ba atomic molar ratio of 2:1:1:0.5 to prepare a 2 mol / L mixed salt solution. A 2 mol / L aqueous solution of anhydrous Na₂CO₃ was also added as a precipitant. The mother liquor was an aqueous solution dispersed in Al₂O₃. The Al₂O₃ support accounted for 70% of the total catalyst mass.

[0101] The Co / Mn / Al / Ba mixed solution was co-precipitated with a Na2CO3 aqueous solution in a stirred Al2O3 mother liquor at a volume ratio of 1:1. The stirred precipitation solution was maintained at a pH of 8 and a temperature of 30°C. After precipitation, the solution was aged at 30°C for 2 hours. The precipitate was then ball-milled in a mill using aluminum-zirconium grinding balls at a 1:10 precipitate-to-ball ratio. Water was used as a grinding aid at a 100:1 precipitate-to-precipitate ratio. The mixture was ball-milled for 2 hours at room temperature. After ball-milling, the mixture was dried at 120°C for 10 hours. The mixture was then calcined in a muffle furnace at 350°C for 5 hours to obtain a confined catalyst.

[0102] [Example 3]

[0103] Co(NO₃)₂﹒6H₂O, Ce(NO₃)₂﹒6H₂O, and Mg(NO₃)₂﹒6H₂O were dissolved in water at a Co / Ce / Mg atomic molar ratio of 2:1:0.5 to prepare a 2 mol / L mixed salt solution. A 2 mol / L anhydrous Na₂CO₃ aqueous solution was also added as a precipitant. The mother liquor was an Al₂O₃-dispersed aqueous solution. The Al₂O₃ support accounted for 80% of the total catalyst mass.

[0104] The Co / Ce / Mg mixed solution and a Na2CO3 aqueous solution were co-precipitated in a stirred Al2O3 mother liquor at a volume ratio of 1:1. The stirred precipitation solution was maintained at a pH of 8 and a temperature of 30°C. After precipitation, the solution was aged at 30°C for 2 hours. The precipitate was then ball-milled in a mill using aluminum-zirconium grinding balls at a 1:10 weight ratio of precipitate to grinding balls. Water was used as a grinding aid at a 100:1 weight ratio of water to precipitate. The mixture was ball-milled for 2 hours at room temperature. After ball-milling, the mixture was dried at 120°C for 10 hours. The mixture was then calcined in a muffle furnace at 350°C for 5 hours to obtain a confined catalyst.

[0105] [Example 4]

[0106] Co(NO₃)₂﹒6H₂O, a 50% Mn(NO₃)₂ aqueous solution, and NaNO₃ at a Co / Mn / Na atomic molar ratio of 2:1:0.002 were dissolved in water to prepare a 2 mol / L mixed salt solution. This solution was then impregnated onto an Al₂O₃ support in equal volumes multiple times. After impregnation, the mixture was dried at 120°C for 10 hours. It was then calcined in a muffle furnace at 350°C for 5 hours. A 2 mol / L Mg(NO₃)₂﹒6H₂O aqueous solution was prepared at a Co / Mg atomic ratio of 2:0.5. This solution was then impregnated onto the Al₂O₃ support in equal volumes multiple times. After impregnation, the mixture was dried at 120°C for 10 hours. It was then calcined in a muffle furnace at 350°C for 5 hours. The support mass accounted for 80% of the total catalyst mass, resulting in a confined catalyst.

[0107] [Example 5]

[0108] Co(NO₃)₂﹒6H₂O, Ce(NO₃)₂﹒6H₂O, and NaNO₃ were dissolved in water at a Co / Ce / Na atomic molar ratio of 3:1:0.002 to prepare a 2 mol / L mixed salt solution. This solution was then impregnated onto an activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 100°C for 10 hours. The solution was then calcined in a muffle furnace at 350°C for 5 hours. A 2 mol / L Ba(NO₃)₂﹒6H₂O aqueous solution was prepared at a Co / Mg atomic ratio of 2:0.5. This solution was then impregnated onto the activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 120°C for 10 hours. The solution was then calcined in a muffle furnace at 400°C for 5 hours. The support mass accounted for 80% of the total catalyst mass, resulting in a confined catalyst.

[0109] [Example 6]

[0110] Co(NO₃)₂﹒6H₂O, Ce(NO₃)₂﹒6H₂O, and NaNO₃ were dissolved in water at a Co / Ce / Na atomic ratio of 3:1:0.002 to prepare a 2 mol / L mixed salt solution. This solution was then impregnated onto an activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 100°C for 10 hours. It was then calcined in a muffle furnace at 350°C for 5 hours. A 2 mol / L La(NO₃)₃﹒6H₂O aqueous solution was prepared at a Co / La atomic ratio of 2:0.5. This solution was then impregnated onto the activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 120°C for 10 hours. It was then calcined in a muffle furnace at 400°C for 5 hours. The support mass accounted for 70% of the total catalyst mass, resulting in a confined catalyst.

[0111] [Example 7]

[0112] Co(NO₃)₂﹒6H₂O, Ce(NO₃)₂﹒6H₂O, and NaNO₃ were dissolved in water at a Co / Ce / Na atomic ratio of 3:1:0.002 to prepare a 2 mol / L mixed salt solution. This solution was then impregnated onto an activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 100°C for 10 hours. The solution was then calcined in a muffle furnace at 350°C for 5 hours. A 2 mol / L RuCl₃﹒3H₂O aqueous solution was prepared at a Co / Ru atomic ratio of 2:0.1. This solution was then impregnated onto the activated carbon support in equal volumes multiple times. After impregnation, the mixture was dried at 120°C for 10 hours. The solution was then calcined in a muffle furnace at 350°C for 5 hours. The support mass accounted for 70% of the total catalyst mass, resulting in a confined catalyst.

[0113] [Example 8]

[0114] Co(NO₃)₂﹒6H₂O, a 50% aqueous solution of Mn(NO₃)₂, Mg(NO₃)₂.6H₂O, and NaNO₃ were dissolved in water at a Co / Mn / Mg / Na atomic molar ratio of 3:1:0.5:0.002 to prepare a 2 mol / L mixed salt solution. The Co / Mn / Mg / Na mixture was evaporated to dryness at 150°C for 2 hours to form a catalyst precursor. The evaporated powder was placed in a beaker and dispersed in ethyl orthosilicate, ammonia, and water. The mass ratio of the catalyst precursor to the ethyl orthosilicate, ammonia, and water mixture was 1:100, and the volume ratio of ethyl orthosilicate to ammonia and water was 1:5:30. The mixed solution was then heated in a reactor at 180°C for 10 hours. After heating, the mixture was centrifuged at 4000 rpm for 5 minutes, filtered, dried, and calcined. The drying conditions were: 120°C for 10 h and the calcination conditions were: 400°C for 3 h to obtain the eggshell catalyst.

[0115] [Example 9]

[0116] Co(NO₃)₂﹒6H₂O, a 50% aqueous solution of Mn(NO₃)₂, Ba(NO₃)₂.6H₂O, and NaNO₃ were dissolved in water at a Co / Mn / Ba / Na atomic molar ratio of 3:0.001:0.5:0.002 to prepare a 2 mol / L mixed salt solution. The Co / Mn / Ba / Na mixture was evaporated to dryness at 150°C for 2 hours to form a catalyst precursor. The evaporated powder was placed in a beaker and dispersed in ethyl orthosilicate, ammonia, and water. The mass ratio of the catalyst precursor to the mixture of ethyl orthosilicate, ammonia, and water was 1:100, and the volume ratio of ethyl orthosilicate to ammonia and water was 1:5:30. The mixed solution was then heated in a reactor at 200°C for 10 hours. After heating, the mixture was centrifuged at 4000 rpm for 5 minutes, filtered, dried, and calcined. The drying conditions were: 120°C for 10 h and the calcination conditions were: 400°C for 5 h to obtain the eggshell catalyst.

[0117] [Example 10]

[0118] Co(NO₃)₂﹒6H₂O, a 50% aqueous solution of Mn(NO₃)₂, Ba(NO₃)₂.6H₂O, and NaNO₃ were dissolved in water at a Co / Mn / Ba / Na atomic molar ratio of 3:0.001:1:0.002 to prepare a 2 mol / L mixed salt solution. The Co / Mn / Ba / Na mixture was evaporated to dryness at 150°C to form a catalyst precursor. The evaporated powder was placed in a beaker and dispersed in ethyl orthosilicate, ammonia, and water. The mass ratio of the catalyst precursor to the mixture of ethyl orthosilicate, ammonia, and water was 1:100, and the volume ratio of ethyl orthosilicate to ammonia and water was 1:5:30. The mixed solution was then heated in a reactor at 180°C for 10 hours. After heating, the mixture was centrifuged at 4000 rpm for 5 minutes, filtered, dried, and calcined. The drying conditions were: 120°C for 10 h and the calcination conditions were: 400°C for 5 h to obtain the eggshell catalyst.

[0119] [Comparative Example 1]

[0120] Co(NO₃)₂﹒6H₂O, a 50wt% aqueous solution of Mn(NO₃)₂, and Mg(NO₃)₂﹒6H₂O were dissolved in water at a Co / Mn / Mg atomic molar ratio of 2:1:0.5 to create a mixed salt solution with a total metal ion concentration of 2 mol / L. This solution was then co-precipitated with a 2 mol / L aqueous solution of Na₂CO₃ at a volume ratio of 1:1. The stirred precipitation solution was maintained at a pH of 8 and a temperature of 30°C. After precipitation, the solution was aged at 30°C for 2 hours. After aging, the mixture was filtered and dried at 120°C for 10 hours. The solution was then calcined in a muffle furnace at 350°C for 5 hours to obtain the catalyst.

[0121] Effect Example 1

[0122] 1.5 g of the catalyst prepared in Examples 1 to 10 with a mesh size of 40-60 was physically mixed with 1.5 g of quartz sand with a mesh size of 40-60 and loaded into a reactor. The reduction temperature was set to 300° C., the reduction pressure was 1 bar, the time was 5 h, the reducing gas was 10% H2 / N2 (v / v), and the space velocity was 8000 ml.g -1 .h -1 After the reduction was completed, the reaction was switched to a synthesis gas with a molar ratio of H2 / CO of 0.5. The reaction temperature was set to 260°C, the pressure was 5 bar, and the space velocity was 1000 ml.g -1 .h -1 , the results are shown in Table 1.

[0123] Table 1 Example catalyst reaction results

[0124]

[0125]

[0126] As can be seen from Table 1, the use of the confined catalyst or eggshell-type Co-based catalyst described in the present invention can significantly reduce the selectivity of CO2 in the FTO reaction, as low as 12.8%; while maintaining high CO conversion rate and olefin selectivity, the product distribution is more economical. In addition, the catalyst prepared by the modification process of the present invention has good stability, and the catalyst activity does not show obvious deactivation within 2000 hours. At the same time, the modification process is relatively simple and can be applied industrially.

[0127] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A FTO catalyst that effectively inhibits CO2, characterized in that The FTO catalyst is a Co-based catalyst, which includes an active component and a carrier. The active component includes Co oxide and M1 oxide. The M1 includes one or more of Mn, Na, and Al. The molar ratio of Co to M1 is 1:10 to 10:

1. The Co-based catalyst is a confined Co-based catalyst or an eggshell-type Co-based catalyst.

2. The FTO catalyst according to claim 1, characterized in that In the confined catalyst, M1 further comprises one or more of Ce, Zr, and K; Preferably, the active component in the confined catalyst further includes M2 oxide; Preferably, the M2 includes one or more of alkali metal elements, alkaline earth metal elements, noble metals, and rare earth metal elements; Preferably, the molar ratio of Co to M2 is selected from 3:1 to 30:1; Preferably, M1 in the eggshell-type catalyst further includes one or more of alkaline earth metal elements, noble metals, rare earth metal elements, and Si.

3. The FTO catalyst according to claim 1, characterized in that The carrier component is selected from at least one of SiO2, Al2O3 or activated carbon; Preferably, the carrier accounts for 70% to 80% by mass of the Co-based catalyst.

4. The method for preparing the FTO catalyst according to any one of claims 1 to 3, characterized in that: The confined Co-based catalyst is prepared by an equal volume impregnation method or a deposition precipitation method; Preferably, the preparation of the catalyst by the equal volume impregnation method comprises the following steps: S11: providing soluble salts corresponding to Co, M1 and / or M2, and mixing them with a solvent to obtain a first mixed solution; S12: impregnating an equal volume of the first mixed solution onto the support, and drying and calcining the mixture; Preferably, the method for preparing the catalyst by sedimentation precipitation method comprises the following steps: S21: providing soluble salts corresponding to Co, M1 and / or M2, and mixing them with a solvent to obtain a second mixed solution; S22: The second mixed solution and the precipitant are co-precipitated on the carrier for sedimentation. After the precipitation is completed, the precipitate is aged, ball-milled, mixed, dried, and calcined.

5. The method according to claim 4, characterized in that The soluble salts of Co, M1, and M2 include one or more of the corresponding nitrates, chlorides, sulfates, and carbonates; Preferably, the concentration of total metal ions in the first mixed solution is 0.5 to 5 mol / L; Preferably, the concentration of total metal ions in the second mixed solution is 0.5 to 5 mol / L; Preferably, the precipitant is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and ammonia solution; Preferably, the coprecipitation conditions are: the coprecipitation temperature is 20 to 40° C.; and / or the coprecipitation pH is 7 to 9; Preferably, the aging temperature is 20-40° C.; and / or the aging time is 1-3 hours.

6. The method according to claim 4, characterized in that The specific steps of ball milling and mixing include: mixing the aged precipitate with grinding balls and / or grinding aids and then using a ball mill to perform ball milling and mixing; Preferably, the mass ratio of the precipitate to the grinding balls is 1:5 to 20; Preferably, the mass ratio of the precipitate to the grinding aid is 1:50-200; Preferably, the drying temperature in step S12 or S22 is 80-150° C.; and / or the drying time is 5-20 hours; And / or, the calcination temperature is 300° C. to 370° C.; and / or, the calcination time is 2 to 10 hours.

7. The preparation method according to claim 4, characterized in that The eggshell catalyst is prepared by a hydrothermal method; The specific steps include: S31: providing soluble salts corresponding to Co and M1, and mixing them with a solvent to obtain a third mixed solution; S32: evaporating the third mixed liquid to dryness to obtain a catalyst precursor; S33: uniformly dispersing the catalyst precursor in a fourth mixed solution comprising a silicon source, aqueous ammonia, and water, and heating the mixture. After heating, the mixture is centrifuged, dried, and calcined. Preferably, the soluble salts corresponding to Co and M1 include one or more of nitrate, chloride, sulfate, and carbonate; Preferably, the concentration of total metal ions in the third mixed solution is 0.5 to 5 mol / L; Preferably, the silicon source includes one or more of tetraethyl orthosilicate, ethyl orthosilicate, dichlorodimethylsilane, methyltrimethoxysilane, and octadecyltrimethylsilane; Preferably, the volume ratio of the silicon source, aqueous ammonia and water in the fourth mixed liquid is 1:2-8:20-40; Preferably, the evaporation temperature in step S32 is 130-170° C.; and / or the evaporation time is 1-4 hours; Preferably, the heating temperature in step S33 is 160-220° C.; and / or the heating time is 8-14 hours; Preferably, the drying temperature in step S33 is 80-150°C; and / or the drying time is 10-20 hours; preferably, the roasting temperature in step S33 is 300-400°C; and / or the roasting time is 3-10 hours.

8. Use of the FTO catalyst according to any one of claims 1 to 3 or the FTO catalyst prepared by the method according to any one of claims 4 to 7 in preparing olefins from synthesis gas.

9. The use according to claim 8, characterized in that The application includes one or more of the following: 1) The CO conversion rate in olefin production from synthesis gas is 48.3-72.2%; 2) The selectivity of CO2 in olefin production from synthesis gas is 12.8-33.3%; 3) The selectivity of olefins in the preparation of olefins from synthesis gas is 58.3-66.9%.

10. The use according to claim 8, characterized in that The application comprises the following steps: mixing the FTO catalyst according to any one of claims 1 to 3 with quartz sand, loading the mixture into a reactor, reducing the loaded catalyst under a reducing atmosphere, and then introducing synthesis gas to react; Preferably, the reaction temperature is 200-300°C; and / or the reaction pressure is 1 bar-4 MPa; and / or the reaction space velocity is 500-6000 ml.g -1 .h -1 .